The Subsurface Coherent Rock Content of the Moon as Revealed by Cold‐Spot Craters. Issue 12 (21st December 2019) - Elder, C. M.; Douglass, B.; Ghent, R. R.; Hayne, P. O.; Williams, J.‐P.; Bandfield, J. L.; Costello, E.
Abstract: A recently identified class of young lunar craters, cold‐spot craters, provides an optimal data set for probing the subsurface rock content on the Moon. Rocks, or lack of rocks, in crater ejecta have long been used as indicators of regolith thickness. However, the rockiness of crater ejecta depends on the subsurface rock content, crater excavation depth, and crater age. Cold‐spot craters are surrounded by a low thermal inertia signature that fades within 1 Myr, so any rocks in the proximal ejecta blanket have not yet been broken down or buried. Thus, the rock abundance in the proximal ejecta blankets of cold‐spot craters is affected only by the subsurface rock content of the target and the crater excavation depth, not the age of the crater. We show that an abrupt transition between fine‐grained regolith and underlying coherent rock cannot explain the observed rock abundance. Instead, we assume that the volume fraction of coherent rock (in contrast to fine‐grained regolith) increases exponentially in the lunar subsurface and use the observed Diviner rock abundance in cold‐spot crater ejecta to solve for the " e ‐folding" depth over which the volume fraction of rock increases. In general, the subsurface rock content is higher in the maria than in the highlands consistent with more recent resurfacing of the maria. However, the highlands show a wider range of subsurface rock content values overall including some overlapping those of the maria. Some of this variability appears to be associated with the Orientale basin and possibly with several cryptomare deposits. Key Points: Cold‐spot craters are ideal for probing the subsurface rock content on the Moon, because they formed recently The subsurface rock content is higher in the maria than in the highlands, as expected The highlands show a wider range of subsurface rock content than the maria